The mystery of the writing process: a comparison of mechanistic and developmental organic writing - Yaacob, Solehah@Nik Najah Fadilah (2018)
Every writer knows putting words on paper is a difficult task. Sometimes the difficulties become insurmountable. He got himself into a state of frustration in the process of writing when the flow of ideas stops. A writer got stuck, bangs his head against the wall for long hours instead of writing. His struggle becomes futile without getting the desired result. He is helpless in spite of being armed with knowledge and language ability to execute his task. The objective is primarily to understand the cognitive processes at work in the process of writing employing different approaches: mechanistic writing model and developmental organic writing model. This understanding is derived and inferred from some learning theories such as the behaviorist and mechanistic models coupled with issues related to the functions of brains and ‘mind’ in the process of writing as expounded by some known linguists and writers. It is hoped that by knowing the cognitive processes at work in the process of writing anyone who intends to write can benefit in terms of enhancing his writing skill and making writing a challenging and enjoyable task.